Kompetensi Diaken berdasarkan 1 Timotius 3:8-13 - Tari, Ezra (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
The competence of a deacon in 1 Timothy 3: 8-13 are the requirements that should get the attention of the church. In this article, the author describes the duties and responsibilities of a deacon. The purpose of this study is that the deacons will understand their duties and responsibilities. The author intends to reposition deacons who serve the marginalized. The research method used is hermeneutic. There are four results in this study. First is being able to resist temptation. Second is flawless. Third is trustworthiness.                                                             Fourth is being role models for family members